The arts, culture, and the evolution of the White Rose resistance - Lloyd, A (Taylor & Francis, 2023)
This Introduction to the special issue The White Rose and the Uses of Culture addresses the role of culture and the arts in the history and reception of the Weiße Rose resistance circle. Literature, music, and the visual arts were at the centre of the student resisters’ lives: they brought and bound them together, and profoundly influenced their ways of seeing the world. They were also the subject of Professor Kurt Huber’s academic research. This essay examines some of the cultural influences on, and interests of, the core members of the resistance group and considers how their cultural engagement might better be understood as an integral part of their individual and collective decision to resist Nazism. It also provides a brief overview of the eight articles in the special issue and sets out some of the key questions they ask about the uses of culture within the White Rose resistance pamphlets and beyond.